The Potential of β Carbolin Alkaloids to Hinder Growth and Reverse Chloroquine Resistance in Plasmodium falciparum - Zaid O IBRAHEEM; Roslaini ABDUL MAJID; Sabariah MOHD NOOR; Hasidah MOHD SIDEK; Rusliza BASIR (Iranian Journal of Parasitology, 2015)
Background: Nowadays, scourge of malaria as a fatalistic disease has increased due to emergence of drug resistance and tolerance among different strains of Plasmodium falciparum. Emergence of chloroquine (CQ) resistance has worsened the calamity as CQ is still considered the most efficient, safe and cost effective drug among other antimalarials. This urged the scientists to search for other alternatives or sensitizers that may be able to augment CQ action and reverse its resistance.